Income Elasticity of Housing Demand - Carliner, Geoffrey (The Review of Economics and Statistics, 1973)
This paper estimates a housing demand function from a four year panel study.The findings indicate that the income elasticity of housing demand is around .6 or .7 for owners and around .5 for renters.This means that the percentage of income spent on housing declines as income rises, and that the property tax falls more heavily on the poor than on the rich.This finding differs from earlier studies which were based on city averages rather than panel studies, and is therefore more reliable.The study also found that, other things equal, the old demand more housing than the young, whites more than nonwhites, and female headed households more than male headed households.